(untitled) (Research, Society and Development, 2022)
The present study intends to evaluate the quality control of blood components performed in a Hemotherapy Center in a region of northeastern Brazil. Methods: The research was carried out in the Quality Control laboratory of a Hemotherapy Center in a region of northeastern Brazil, from January to December 2020. This is a retrospective analysis of the monthly reports prepared in the quality and support laboratory for the diagnosis, obtained from analyzes of packed red blood cells (CH), platelets (PC) and plasma (CPF) bags. Using the Microsoft Excel 2019 program (16.0), of September 24, 2018) a database was created, in which specific information for each type of concentrate was recorded. Results and discussion: Blood components are the result of physical processes, such as the concentration of red blood cells, fresh frozen plasma, platelet concentrate and cryoprecipitate; blood products, on the other hand, are made through the industrialization of plasma. In this sense, it is extremely important that there is an observation and an adequate analysis of the quality of the blood components, which will be used in hemotherapy as therapeutic procedures. Conclusion: With this research, we were able to observe that even with all the analysis and quality control of blood components, the competent bodies must seek to act more rigorously and, in this sense, focusing on the issue of improving new techniques is essential.